Analysis of the Level of Plasmid-Derived mRNA in the Presence of Residual Plasmid DNA by Two-Step Quantitative RT-PCR - Barbara Ahlemeyer; Claudia Colasante; Eveline Baumgart-Vogt (Methods and Protocols, 2020)
In transfection experiments with mammalian cells aiming to overexpress a specific protein, it is often necessary to correctly quantify the level of the recombinant and the corresponding endogenous mRNA. In our case, mouse calvarial osteoblasts were transfected with a vector containing the complete Pex11β cDNA (plasmid DNA). The Pex11β mRNA level, as calculated using the RT-qPCR product, was unrealistically higher (>1000-fold) in transfected compared to non-transfected cells, and we assumed that there were large amounts of contaminating plasmid DNA in the RNA sample. Thus, we searched for a simple way to distinguish between plasmid-derived mRNA, endogenous genome-derived mRNA and plasmid DNA, with minimal changes to standard RT-PCR techniques. We succeeded by performing a plasmid mRNA-specific reverse transcription, and the plasmid cDNA was additionally tagged with a nonsense tail. A subsequent standard qPCR was conducted using appropriate PCR primers annealing to the plasmid cDNA and to the nonsense tail. Using this method, we were able to determine the specific amount of mRNA derived from the transfected plasmid DNA in comparison to the endogenous genome-derived mRNA, and thus the transfection and transcription efficiency.